Import and Export of Drugs- Processor Aspects - Roop Raj (International journal of economic perspectives, 2016)
Liberalization “measures in the pharmaceutical sector have brought about major changes in the industrial licensing policy; Exports of formulations have grown faster while their imports have not registered any jump, keeping the balance of trade positive. But there has been a decline in domestic production of bulk drugs and a growth in imports because the industry is moving away from intermediates and is focusing on bulk drugs at the high end of the value chain.”